Penerapan Jaringan Syaraf Tiruan Untuk Identifikasi Citra Iris Mata Menggunakan Algoritma Delta Rule - Hasibuan, Putry Hetty (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
The development of technology today has greatly influenced the development of science, one of which is in the recognition of iris patterns. When compared to fingerprints, the iris has the advantage of being protected by the eyelids and is more stable as the human age increases. The iris in human vision functions to regulate the size of the pupil and regulate the amount of light entering the eye. If observed more deeply the iris has unique characteristics of each individual. so that the iris can be used as a biometric mark for identification. Artificial Neural Network (ANN) is a tool to solve problems, especially in the field and iris pattern recognition. In general, Artificial Neural Network has a working principle that mimics the human neural network system, weighs the actions to be taken, and makes decisions like humans. Iris recognition can be used as an alternative if the introduction of fingerprints as a biometric identity fails. in this study, iris recognition uses the Dela Rule algorithm. The Delta Rule algorithm has the advantage of being able to check errors during the learning process. This will certainly make the Delta Rule algorithm have a high level of accuracy in iris pattern recognition.